More new publications from CTA 3 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
More new publications from CTAMarketability of Caribbean minor fruits edited by St Clair Forde, Proceedings of a CARDI/CTA seminar.Available from: CARDI, UWI Campus, St Augustine, Trinidad and Tobago, West Indies.Fax: +1 868 645 1208.